ANALISA HUBUNGAN LEARNING ORGANIZATION TERHADAP COMPETITIVE ADVANTAGE DALAM MENINGKATKAN FINANCIAL PERFORMANCE PADA SEKTOR PERHOTELAN DI JAWA TIMUR - Yunike, Hanna (Business Accounting Review, 2016)
The purposes of this research was to know the positive and significant influence of learning organization towards competitive advantage, competitive advantage towards financial performance, and learning organization towards financial performance on hospitality sector in East Java. The data analysis technique in this research used Partial Least Square (PLS) with calculation process assisted by SmartPLS software application program to process the questionnaires data. The results of this research showed there was positive and significant influence of learning organization towards competitive advantage; competitive advantage towards financial performance; learning organization towards financial performance; but competitive advantage was able to mediate the relationship between learning organization and financial performance.